2012
DOI: 10.1107/s1600536812022027
|View full text |Cite
|
Sign up to set email alerts
|

Tris[2-(2H-indazol-2-yl)ethyl]amine

Abstract: The title tertiary amine, C27H27N7, a potential tripodal ligand for coordination chemistry, crystallizes with the central N atom located on a threefold axis of a trigonal cell. The gauche conformation of the N(amime)—CH2—CH2—N(indazole) chain [torsion angle = −64.2 (2)°] places the pendant 2H-indazole heterocycles surrounding the symmetry axis, affording a claw-like shaped mol­ecule. Two symmetry-related indazole planes in the mol­ecule make an acute angle of 60.39 (4)°. The lone pair of the tertiary N atom is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ring closures of this type have been reported before. Ovalle et al reported on the attempted synthesis of L 4 using a synthesis similar to the one reported here [25]. In their study they attempted to purify the polydentate amine using column chromatography (silica).…”
Section: Secondary Amine Chemistry (L 4 )mentioning
confidence: 96%
“…Ring closures of this type have been reported before. Ovalle et al reported on the attempted synthesis of L 4 using a synthesis similar to the one reported here [25]. In their study they attempted to purify the polydentate amine using column chromatography (silica).…”
Section: Secondary Amine Chemistry (L 4 )mentioning
confidence: 96%